Assessing the Risk/Benefit at Status Epilepticus Onset: The Prognostic Scores. Issue 5 (September 2020) - Alvarez, Vincent; Rossetti, Andrea O.
Abstract : Summary: Status epilepticus is a medical emergency with a wide range of etiology, severity, and outcome. Different scores that can help in the stratification of a patient's risk of mortality have been published. This study describes and compares the three available scores (Status Epilepticus Severity Score, Epidemiology-Based Mortality Score in Status Epilepticus and Encephalitis, Nonconvulsive, Diazepam resistance, Imaging, Tracheal intubation).